Islamic Education in The Inclusive School: Experimental Study of The Application of Differentiated Instruction For Slow Learners - Anita Aisah; Dwi Santosa AB (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2019)
One of competences that teachers need to achieve is readiness to teach students with various characteristics. Teachers of Islam religion subject in some schools do not have adequate competence to teach diverse students. Slow learners are mostly found in both regular and inclusive schools. The researchers offer a method which can adjust a curriculum to be compatible to students’ conditions namely differentiated instruction method or DI to be applied in Islam religion subject. The goal of this research serves to figure out whether or not DI method can improve learning motivation and achievement for slow learners. The research respondents were slow learners in regular schools. It applied pretest-posttest experiment research method. The research was conducted in April and May, 2019 in Primary School XX in Bantul regency. Data were collected using observation technique, pretest in the form of knowledge test covering previous theme namely sholat (praying) and posttest in the form of the result of knowledge test. Finding revealed that two out of three slow learners did not attend complete experiment process so that there was only one student left. There was a significant increase on knowledge score between pretest and posttest (sig 0,000). This student’s learning motivation improved as well from someone who was previously crying when being asked to come to the front of the class or to answer questions becoming a student who was more communicative.